Water Resources Management and Sustainability - Kumar, Pankaj; Nigam, Gaurav Kant.; Sinha, Manish Kumar; Singh, Anju. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Water is the elixir of life and is crucial for sustainable development. Earlier, it was considered to be a limitless or at least a fully renewable natural resource. During the past 20 years, however, there has been tremendous pressure on this precious natural resource mainly due to rapid urbanization, industrialization and the increase in the human population. Together, these have resulted in increasing demand for irrigation, industrial, and household purposes to meet supply-chain requirements. Keeping in mind the scarcity of available water resources in the near future and its impending threats, it has become imperative on the part of scientists in hydrology and allied disciplines such as geography, landscape planning, sustainability science etc. Regional planners and supply chain management experts also must be involved in studying the spatial and temporal nature of the growing demand for water and the future availability for its judicial use and sustainable management. A primary intent of the book is to provide comprehensive scientific knowledge base on water resource management and sustainability. It covers geo-engineering and scientific problems, case studies, and sustainable solutions in the water resources management domain. Additionally and of equal importance, the chapters of the book provide in-depth coverage on water resource vulnerability, water quality, wastewater treatment, application of remote sensing and geographical information systems hydrological modeling and harvesting, climate variability and runoff, sediment discharge and irrigation planning, community participation in water governance, internet of things and machine learning applications for sustainable water resources management. This practical, state-of-the-art reference book is a valuable resource for students, researchers, scientists, policymakers, spatio-temporal designers of water resource systems, various stake holders interested in hydro-climatology and sustainable water resources management.
Water Resources, Livelihood Vulnerability and Management in Rural Desert Communities of Jaisalmer, India -- Mining Related PCB in Wetland Sediments of the River Lippe (North Rhine-Westphalia, Germany) -- Wastewater Treatment Plants Advantage to Combat Climate Change and Help Sustainable Water Management -- Rethinking Community Water Governance: What Shapes Local Level Decision Making? A Case of Selected Communities in the Wassa Amenfi East District of the Western Region, Ghana -- Impact of Evaporation Losses from on-farm Reservoirs on the Economics of the Farming System -- Estimating Sediment Rate through Stage-Discharge Rating Curve for Two Mountain Streams in Sikkim, India -- Relative Contribution of Climate Variables on Long-term Runoff using Budyko Framwork -- Irrigation Planning with Fuzzy Parametric Programming Approach -- Application of High Resolution Hydrological & Hydraulic Models for Sustainable Water Resources Management -- Development of Three-Dimensional Mathematical Groundwater Flow Model of Raipur City Area, Chhattisgarh, India -- Flood Modeling Using HEC-RAS for Purna River, Navsari District, Gujarat, India -- Hydrological Parameter Estimation for Water Balance Studies Using SWAT Model -- Groundwater Potential Mapping using Maximum Entropy -- Application of remote sensing and GIS in floodwater harvesting for groundwater development in the upper delta of Cauvery River Basin, Southern India -- Strategic evaluation of multi-objective water quality monitoring network using GIS-AHP model in a large River system -- Determination of Root Causes for Drying of Kanari River System by Integration of Multi-temporal Land Use Land Cover mapping in GIS Environment -- Impacts of Climate Variability on Urban Rainfall Extremes Using Statistical Analysis of Climatic Variables for Change Detection and Trend Analysis -- An Analysis of Textural Characteristics and Depositional Environment of Sediments In The Gumti River, Tripura, India -- Morphometric Analysis and Geohydrological Inference of Bhilangna Drainage Basin, Uttarakhand (India) using Remote Sensing and GIS techniques -- Geospatial Analysis of Kosi River Course From 1998 To 2018 -- Internet of Things and Machine Learning Application for a Remotely Operated Wetland Siphon System during Hurricanes -- AHP based Site Suitability Analysis for Water Harvesting Structure Using geospatial technique -- Attaining Optimal Sustainability for Urban Wastewater Management Using Open-source tools like QGIS, EPANET, and WATERNETGEN.
Keywords: Environmental management; Water; Hydrology; Sustainability; Geographic information systems; Geotechnical engineering; Environmental monitoring; Environmental Management; Water; Sustainability; Geographical Information System; Geotechnical Engineering and Applied Earth Sciences; Environmental Monitoring